Single-cell transcriptomic landscape reveals the role of intermediate monocytes in aneurysmal subarachnoid hemorrhage - Meng, Ningqin; Su, Ying; Ye, Ziming; Xie, Xufeng; Liu, Ying; Qin, Chao (Frontiers in Cell and Developmental Biology, 2024)
Objective: Neuroinflammation is associated with brain injury and poor outcomes after aneurysmal subarachnoid hemorrhage (SAH). In this study, we performed single-cell RNA sequencing (scRNA-seq) to analyze monocytes and explore the mechanisms of neuroinflammation after SAH.We recruited two male patients with SAH and collected paired cerebrospinal fluid (CSF) and peripheral blood (PB) samples from each patient. Mononuclear cells from the CSF and PB samples were sequenced using 10x Genomics scRNA-seq. Additionally, scRNA-seq data for CSF from eight healthy individuals were obtained from the Gene Expression Omnibus database, serving as healthy controls (HC). We employed various R packages to comprehensively study the heterogeneity of transcriptome and phenotype of monocytes, including monocyte subset identification, function pathways, development and differentiation, and communication interaction. Results: (1) A total of 17242 cells were obtained in this study, including 7224 cells from CSF and 10018 cells from PB, mainly identified as monocytes, T cells, B cells, and NK cells. (2) Monocytes were divided into three subsets based on the expression of CD14 and CD16: classical monocytes (CM), intermediate monocytes (IM), and nonclassical monocytes (NCM). Differentially expressed gene modules regulated the differentiation and biological function in monocyte subsets. (3) 2 Compared with healthy controls, both the toll-like receptor (TLR) and nod-like receptor (NLR) pathways were significantly activated and upregulated in IM from CSF after SAH. The biological processes related to neuroinflammation, such as leukocyte recruitment and immune response regulation, were also enriched in IM. These findings revealed that IM may play a key role in neuroinflammation by mediating the TLR and NLR pathways after SAH. Interpretation: In conclusion, we establish a single-cell transcriptomic landscape of immune cells and uncover the heterogeneity of monocyte subsets in SAH. These findings offer new insights into the underlying mechanisms of neuroinflammation and therapeutic targets for SAH.